Awareness of Food Handlers on Food Packaging Safety during Business in Taman Puterajaya Telipok Ria, Kota Kinabalu. - Siti Hajar Zakariah,; Abu Kasim, Fazrulniezam Qasmin (Research and Innovation in Technical and Vocational Education and Training, 2023)
This study entitled "Awareness of Food Handlers on Food Packaging Safety During Business in Taman Puterajaya Telipok Ria, Kota Kinabalu" aims to examine food packaging safety practices and the level of food packaging safety awareness among food handlers in Taman Puterajaya Telipok Ria, Kota Kinabalu. The population of this study consists of food handlers who run businesses and the number of respondents is 43 people. This study uses a quantitative approach that uses a questionnaire instrument to obtain research data and information. Study data were analyzed using Statistical Packages for the social sciences (SPSS) version 25.0 to obtain the mean value, standard deviation and level of correlation interpretation. The results show that the level of awareness of food handlers in food packaging safety practices and the level of food packaging safety awareness among the community is very high. In addition, this study also shows that the awareness of food handlers in maintaining the safety of food provided is at a high level. This shows that these food handlers have a high awareness in maintaining the safety of food packaging provided before the food is delivered to customers.